Mating aggregations and mating success in the flower thrips, Frankliniella schultzei (Thysanoptera: Thripidae), and a possible role for pheromones - M. Milne (2018)
Aggregations of Frankliniella schultzei males were observed on the corollas of Hibiscus rosasinensis and Gossypium hirsutum flowers in southeast Queensland. Aggregations were seen only on the upper surfaces of corollas but may have occurred on other flower parts, which were hidden from view. Conspecific females entered aggregations and a small proportion of them mated [18% (n = 163), H. rosasinensis; 30% (n = 181), G. hirsutum]. Most females (87and 72%, respectively) that did not mate in aggregations walked to other flower parts. Behavior was difficult to observe on these parts, but mating was sometimes observed there. The number of females that landed within aggregations on the upper surfaces of both H. rosasinensis and G. hirsutum corollas was highly correlated with the number of males (r = 0.88, r = 0.93, respectively; P < 0.001). Significantly more mating pairs were observed in high-density aggregations (mean ± SE, 1.10 ± 0.22 and 4.44 ± 0.48, respectively) than in low-density aggregations (0.37 ± 0.11 and 1.67 ± 0.29, respectively) (P < 0.05) on flowers of both species. More F. schultzei females were attracted to sticky traps baited with live conspecific males set among flowering Ipomoea indica (mean ± SE, 8.83 ± 0.32) and G. hirsutum (10.90 ± 0.79) plants than to control traps (0.10 ± 0.05 and 0.70 ± 0.25, respectively) (P < 0.05), presumably in response to male-produced pheromones. Significantly more females were attracted to traps with high male densities than to traps with low densities. We found no statistical evidence that aggregation size influenced mating success (proportion males that mated). Mating success, however, should be evaluated with respect to mating on all flower parts and not just the upper surfaces of corollas. The results of this study constitute the first behavioral evidence for an attractant sex pheromone in thrips.